1998
DOI: 10.1080/001401398185965
|View full text |Cite
|
Sign up to set email alerts
|

Using leg muscles as shock absorbers: theoretical predictions and experimental results of drop landing performance

Abstract: The use of muscles as power dissipators is investigated in this study, both from the modellistic and the experimental points of view. Theoretical predictions of the drop landing manoeuvre for a range of initial conditions have been obtained by accounting for the mechanical characteristics of knee extensor muscles, the limb geometry and assuming maximum neural activation. Resulting dynamics have been represented in the phase plane (vertical displacement versus speed) to better classify the damping performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 6 publications
2
40
0
2
Order By: Relevance
“…However, Fig. 7 shows clearly that, even though it takes longer (about 0.25 s) for the jumper COM velocity vector to become tangent to the landing surface as a result of the landing being cushioned by the leg muscles (Minetti et al [30]), eventually the EFH experienced by the board and COM are the same. Figure 8 shows how the EFH experienced by the jumper varies with landing position along the surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Fig. 7 shows clearly that, even though it takes longer (about 0.25 s) for the jumper COM velocity vector to become tangent to the landing surface as a result of the landing being cushioned by the leg muscles (Minetti et al [30]), eventually the EFH experienced by the board and COM are the same. Figure 8 shows how the EFH experienced by the jumper varies with landing position along the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Minetti et al [30] have shown that the maximum value of EFH an elite jumper's legs can absorb is only 1.5 m. Clearly EFHs greater than this cannot be considered to be safe. Therefore this value was adopted by the USTPC [31] as a landing design limit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minnetti et al [10] discovered that dynamic characteristics of landings from different heights are dependent of muscle activation.…”
Section: A N D I N G E R R O R S I N T H E M E N ' S Floor Exercisementioning
confidence: 99%
“…The influence of preactivation on the landing success and the foot stability has been investigated by several researchers [3]. The greatest activity of the lower extremities muscles occurs when hips start to drop [10].…”
Section: A N D I N G E R R O R S I N T H E M E N ' S Floor Exercisementioning
confidence: 99%